2018
DOI: 10.31235/osf.io/ewn2g
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Teacher Practice Spaces: Examples and Design Considerations

Abstract: Abstract:Teacher practice spaces are learning environments, inspired by games and simulations, that allow teachers to rehearse for and reflect upon important decisions in teaching. Practice-based teacher educators use a variety of approaches to simulation in methods courses and other professional learning opportunities, and existing simulations often attempt to holistically replicate authentic teaching conditions. We extend this work by developing new kinds of practice spaces that do not attempt to fully simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Existing literature on designing simulations primarily focuses on process models addressing the steps of designing simulations for specific contexts, for example designing simulation for research purposes (Fink et al , 2021) or designing simulations as teacher practice spaces (Reich et al , 2018). Such frameworks typically outline design steps by referring to specific examples of simulations and often touch on discussing selected characteristics of simulations, such as authenticity.…”
Section: Learning Professional Practices In Higher Educationmentioning
confidence: 99%
“…Existing literature on designing simulations primarily focuses on process models addressing the steps of designing simulations for specific contexts, for example designing simulation for research purposes (Fink et al , 2021) or designing simulations as teacher practice spaces (Reich et al , 2018). Such frameworks typically outline design steps by referring to specific examples of simulations and often touch on discussing selected characteristics of simulations, such as authenticity.…”
Section: Learning Professional Practices In Higher Educationmentioning
confidence: 99%
“…Fully digital simulations, what we refer to as 'practice spaces' (Reich et al, 2018) have a number of potential affordances which makes them useful for integration within teacher education programs. Those within web applications are relatively inexpensive to produce and disseminate, providing opportunities for repeated, targeted practice on specific teaching skills.…”
Section: To Engage In Complex High Leverage Practicesmentioning
confidence: 99%
“…In this study, we introduce the concept of using digital simulations or 'practice spaces' to prepare teacher candidates to facilitate conversations of controversial issues. These practice spaces are digital approximations of real-life professional scenarios that leverage mixed media-videos, images, text, and audio--to enable professional novices to take part in interactive cycles of practice, reflection and feedback in low-stakes environments (Reich et al, 2018) Digital simulations are a well-established tool for building expertise across a wide range of fields and disciplines (Aldrich, 2009). For our purposes here, we define simulation as a learning experience designed to approximate a real-world context in which approximations of phenomena can be experienced by participants, and which responds in some substantive way to participants' actions.…”
mentioning
confidence: 99%
“…A few recent studies have found benefits of games for teacher learning within specialized contexts, such as Game School LA (Garcia and Gomez, 2017), a school based on game design and Convergence Academy (Woodard and Machado, 2017), a digital media arts integration school. Game-based experiences can provide opportunities to practice teaching tasks in low-stakes settings (Reich et al , 2018), yet there is little research on game-based learning for teacher development in public secondary schools, especially within university-based PST education. Kangas et al (2017) noted in their literature review of educational games in the classroom that a focus on “actual practices and processes of teaching – before, during, and after the gameplay” is missing.…”
Section: Practice In Game-based Learningmentioning
confidence: 99%